TINJAUAN YURIDIS TINDAK PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL BERDASARKAN PASAL 27 AYAT (3) UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DIKAITKAN DENGAN KEBEBASAN BERPENDAPAT - Fani Indriani; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Globalization era that we encounter has been the mark of technology growth itself. Globalization became the catalyst for the information technology era to be born. The stream that spread around the world nowdays causing changes in all aspect of human life, especially in developing nations, including Indonesia. In years now, motive of crime also developing in many forms, on of them is defamation, slander, and libel via social media, in Indonesia this is known as one of the cyber crimes. And has been obliged under law as state in Article of section (3) of Act No. 11 of 2008 stating Informastion and Electronic Transaction. The freedom of speech which has been regulated under of Act Perss No 40 of 1999, is the rights of every humas but it should be taking every responsibly just as stated on the Article 19 of Universal Declaration of Human Right and Acticle 29 in United Nations (UN).Keywords : Defamation,Salander, and Liber, Social Media, Constitution.